FEATURES OF DIALECTS OF THE KOREAN LANGUAGE ACCORDING TO THE CLASSIFICATION - Azimova Amira Muminovna; Olimjonova Asalabonu Ziyodjonovna (American Journals, 2023)
Dialect is one of the most used systems of speech communication in the Korean language, being a special means to establish contact with the interlocutor. The study of dialects, in particular dialects of the Korean language, is an invaluable marker of the development of any language, its origin and historical development, and also makes it possible to trace the change and formation of words existing in the modern form of the language. In addition, dialects allow you to get into the essence of the various social and cultural layers that make up the linguistic society. Languages and dialects live and develop in continuous and close interaction, which affects all sides and levels of interacting languages.
Keywords: Literary Korean, geographical distribution, Pyongyang dialect, Yukchi dialect, Hamgyong dialect, Kore Mar, Kore Saram.